The Role of Proteasome Inhibition in Nonsmall Cell Lung Cancer. (4th May 2011) - Escobar, Mauricio; Velez, Michel; Belalcazar, Astrid; Santos, Edgardo S.; Raez, Luis E.
Abstract : Lung cancer therapy with current available chemotherapeutic agents is mainly palliative. For these and other reasons there is now a great interest to find targeted therapies that can be effective not only palliating lung cancer or decreasing treatment-related toxicity, but also giving hope to cure these patients. It is already well known that the ubiquitin-proteasome system like other cellular pathways is critical for the proliferation and survival of cancer cells; thus, proteosome inhibition has become a very attractive anticancer therapy. There are several phase I and phase II clinical trials now in non-small cell lung cancer and small cell lung cancer using this potential target. Most of the trials use bortezomib in combination with chemotherapeutic agents. This paper tends to make a state-of-the-art review based on the available literature regarding the use of bortezomib as a single agent or in combination with chemotherapy in patients with lung cancer.